2013
DOI: 10.1016/j.diabres.2012.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Association of retinol binding protein 4 with risk of gestational diabetes

Abstract: Aim We investigated association of maternal retinol binding protein 4 (RBP4) with risk of gestational diabetes (GDM). Methods GDM cases (N=173) and controls (N=187) were selected from among participants of a cohort study of risk factors of pregnancy complications. Early pregnancy (16 weeks on average) serum RBP4 concentration was measured using an ELISA-based immunoassay. Logistic regression was used to estimate unadjusted and adjusted odds ratios (ORs/aORs) and 95% confidence intervals (95%CI). Results Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Similarly, Su et al [12] also reported that serum RBP4 levels are significantly increased in pregnancy. Furthermore, consistent with our findings, previous studies confirmed that patients with GDM had higher median plasma concentration of RBP4 than normal pregnant women [1,12,22,[34][35][36]. However, other studies found that there were no significant differences in serum RBP4 between the controls and those that developed GDM group [14,37,38].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, Su et al [12] also reported that serum RBP4 levels are significantly increased in pregnancy. Furthermore, consistent with our findings, previous studies confirmed that patients with GDM had higher median plasma concentration of RBP4 than normal pregnant women [1,12,22,[34][35][36]. However, other studies found that there were no significant differences in serum RBP4 between the controls and those that developed GDM group [14,37,38].…”
Section: Discussionsupporting
confidence: 82%
“…Gestational diabetes mellitus (GDM), a common complication of pregnancy occurring in 5-10% of all pregnancies, is characterized by glucose intolerance that first appears during pregnancy [1]. One out of every 5 pregnant women in Beijing either had GDM and this constitutes a huge health burden for health services [2].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the correlation between RBP4 and the Brought to you by | University of Windsor Authenticated Download Date | 10/8/15 1:11 PM pathogenesis of GDM has been already debated in the past, showing conflicting results. In some studies a positive correlation between RBP4 and GDM was shown [23,24], while in some other reports it was not [25,26]. The only study conducted in first trimester maternal serum, already previously cited, showed no statistically significant correlation between RBP4 and GDM [14].…”
Section: Discussionmentioning
confidence: 75%
“…Although the association between RBP4 and metabolic dysfunction is well established, studies on the relationship between circulating RBP4 levels and the risk of GDM have yielded inconclusive results [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. For instance, several studies suggested significantly enhanced serum levels of RBP4 in GDM [16,17,19,20,23,[25][26][27][28][29], while some reports showed decreased or no different RBP4 concentrations between GDM serum specimen compared with those of controls [18,21,22,24,29].…”
Section: Introductionmentioning
confidence: 93%